Boundedly Rational versus Optimization-Based Models of Strategic Thinking and Learning in Games - Crawford, Vincent P (Journal of Economic Literature, 2013)
Harstad and Selten's article in this forum performs a valuable service by highlighting the dominance of optimization-based models over boundedly rational models in modern microeconomics, and questioning whether optimization-based models are a better way forward than boundedly rational models. This article complements Rabin's response to Harstad and Selten, focusing on modeling strategic behavior. I consider Harstad and Selten's examples and proposed boundedly rational models in the light of modern behavioral economics and behavioral game theory, commenting on the challenges that remain and the most promising ways forward. (JEL B40, C72, D01, D03, D80)